Motivated to be socially mindful: Explaining age differences in the effect of employees' contact quality with coworkers on their coworker support - Ulrike Fasbender; Anne Burmeister; Mo Wang (Personnel Psychology, 2019)
In this research, we examine how high-quality contact can facilitate employees' coworker support and explain why the benefits of high-quality contact are contingent upon age. First, we employ a social mindfulness lens to decipher the motivational mechanisms of high-quality contact with coworkers on providing coworker support via coworker-oriented perspective taking and empathic concern. Second, we utilize socioemotional selectivity theory to overcome the current age-blind view on workplace interactions and examine the indirect moderating effect of age via future time perspective on the link between contact quality, social mindfulness, and coworker support. We tested our hypotheses based on data from a sample of 575 employees collected in three waves. Results showed that both coworker-oriented perspective taking and empathic concern mediated the positive effects of contact quality on coworker support. The effect of contact quality on coworker-oriented empathic concern was stronger for older employees with a more constrained future time perspective as compared to younger employees with a more extensive future time perspective. Overall, we extend research on aging, workplace interactions, and support behavior by linking the literature on these topics using a social mindfulness lens and by adding employee age and age-related mechanisms as important boundary conditions that qualify the outcomes of positive workplace contact.
Keywords: 650; contact quality; coworker support; future time perspective; social interactions at work; social mindfulness; socio-emotional selectivity theory; workforce aging